The use of medicinal species as non-wood forest products la Tranca Arriba site, San Plácido Parish - Cabrera-Verdesoto, César Alberto (2021)
The interest in knowing and understanding the advantages that natural medicine has on human health has been a constant debate from ancient times to the present. La Tranca Arriba, in San Plácido, Portoviejo, Manabí province, Ecuador is the place where the study was carried out to classify the use of medicinal species as non-timber forest products. Surveys were applied to people ranging from 20 to 80 years of age to estimate the level of use of the species and the significant use of Tramil. The inhabitants of the sector classified the knowledge of the species according to their form, use, and medicinal consumption. Twenty-four species, 23 genus and 18 families were registered; the four species with the highest use value were Matricaria chamomilla L., Mentha rotundifolia L., Origanum vulgare L, and Mentha sativa L., which are used 100% for medicinal purposes. The leaves, with 52.5%, is the most used part and its most frequent use is as infusion, with 67.65%. Regarding the level of significant use, all registered species obtained a value higher than 20% in high cultural acceptance and the natural use of medicinal plants to alleviate physical ailments and conditions.